ADI PARVA, AN INDIAN CLASSIC LITERATURE AS THE SOURCE OF TAMAN GILI DESIGN PHILOSOPHY, A RELIC OF THE KLUNGKUNG KINGDOM OF BALI - I Gede Mugi Raharja (Bajang Institute, 2025)
Adi Parva's classical literature is the beginning of the great epic Mahabharata which originates from ancient Indian culture. Adi Parva entered Indonesia at the same time as the arrival of Hindu culture at the beginning of the AD century, that this literature was well received. It is proven by a temple complex that has been built with the names of the buildings taken from the Mahabharata story in 716 AD, as well as an inscription about a wayang show with Bhima Kumara play in 907 AD. However, this ancient Indian literature entered Indonesia in the form of a verbal art, not a written text. Adi Parva's literary text from India was only translated into ancient Javanese in the 10th century, after which Adi Parva's literary works entered Bali. The most popular thing is the part of Samudramantana story or the churning of the Ksirarnawa Sea using Mount Mandhara. This literary work used as a holy hymn in religious ceremonies, is made in the form of relics and becomes the design philosophy of the royal garden. This article was written based on the results of several studies using hermeneutics approach, then summarized and a deeper study is carried out, to create a stronger study result. The research object of Taman Gili, a relic of the Klungkung Kingdom, is very representative and has a unique design concept. The embodiment of the design is adapted to local Balinese wisdom, even though the design philosophy comes from ancient Indian literature. Adi Parva's texts are translingual and cross-cultural, but have been part of Balinese culture since ancient Balinese times